Teachers’ support for children’s mathematical learning through interactions while playing with a coding toy - Granone, Francesca; Reikerås, Elin (NOMAD Nordic Studies in Mathematics Education, 2023)
This study examines how early childhood education and care teachers can support children’s mathematical learning in the context of playing with a coding toy (a robot). Video recordings of the interactions that occurred between a teacher and four 3- to 5-year-old pupils while they played with a robot (three hours per week over the course of a month) were analysed based on the theoretical framework of semiotic mediation for mathematics education. The results highlight the fact that the coding toy can be viewed as an artefact for accomplishing a didactic mathematical objective through teacher support, including factors such as problem-solving, counting and measuring.